Impacto del crédito privado en el crecimiento económico ecuatoriano durante el periodo 1960-2020, un análisis con series de tiempo - Ludeña Quinche, Jennifer Madeley (2023)
One of the basic enigmas in economics is to know what components of GDP cause economic growth in a country and why countries differ in their growth rates. Thus, several classical authors argue that the private financial sector acts as an essential mechanism to obtain economic growth, since the financial sector stimulates growth and increases employment through capital accumulation and technological innovation, creating greater opportunities for economic activity, particularly in developing countries. In this sense, the main objective of this research is to evaluate the impact of private credit on Ecuadorian economic growth during the period 1960-2020. A methodology with time series and cointegration techniques through VAR and VEC models and Granger causality test was used. Likewise, the World Bank database (2022) was used to acquire the statistical information. Thus, the results confirm that private credit and economic growth are positively and directly correlated. Also, private credit has an impact on economic growth in the short and long term. As for causality, the presence of unidirectional causality of private credit towards economic growth was proved. Therefore, private credit has to develop rapidly through the implementation of policies aimed at innovation and efficiency of financial services, so that Ecuador can achieve positive and sustainable economic growth.